Gene Expression: Sizing It All Up - Woody, Jenna L.; Shoemaker, Randy C. (Frontiers in Genetics, 2011)
Genomic architecture appears to be a largely unexplored component of gene expression. Although surely not the end of the story, we are learning that when it comes to gene expression, size is important. We have been surprised to find that certain patterns of expression, tissue-specific versus constitutive, or high expression versus low expression, are often associated with physical attributes of the gene and genome. Multiple studies have shown an inverse relationship between gene expression patterns and various physical parameters of the genome such as intron size, exon size, intron number and size of intergenic regions. An increase in expression level and breadth often correlates with a decrease in the size of physical attributes of the gene. Three models have been proposed to explain these relationships. However, contradictory results were found in several organisms when expression level and expression breadth were analyzed independently. However, when both factors were combined in a single study a novel relationship was revealed. At low levels of expression, an increase in expression breadth correlated with an increase in genic, intergenic and intragenic sizes. Contrastingly, at high levels of expression, an increase in express